Plasma and Whole Blood Taurine Concentrations in Dogs May Not Be Sensitive Indicators of Taurine Deficiency When Dietary Sulfur Amino Acid Content Is Reduced - Tôrres, Cristina L.; Biourge, Vincent C.; Backus, Robert C. (Frontiers in Veterinary Science, 2022)
Background: Taurine status is impacted by dietary supply of methionine and cysteine (SAA) and possibly intestinal microbial activity, where plasma and whole blood taurine concentrations are currently used to evaluate taurine status. Objective: We determined effects of dietary SAA restriction on rate and extent of taurine depletion of blood and skeletal muscle in dogs of two body sizes, and whether oral antibiotic administration affected the taurine depletion and fecal bile acid excretion of the dogs. Methods: Adult, male, Beagles (n = 6; 10.1-13.1 kg) and larger mixed-breed dogs (n = 6; 28.5-41.1 kg) were given four dry-expanded diets, whereby each successive diet contained lower protein and/or SAA concentration. After receiving the final diet for 44 weeks, all dogs were orally administered a mixture of ampicillin, neomycin sulfate, and metronidazole for 12 weeks. Taurine concentrations were determined every 2 to 4 weeks in venous blood, voided urine, and every 4 to 16 weeks in biopsied semimembranosus muscle. Fecal bile acid excretion before and after antibiotics administration were quantified. Results: When given for 36 weeks the lowest SAA diet, 3.4% methionine and 2.9% cystine, taurine concentrations in whole blood were not different between groups, while taurine in plasma declined (P < 0.05) in large but not in small dogs, and taurine in biopsied muscle decreased (P < 0.05) by 50% in large and by 37% in small dogs. Concentrations of taurine in muscle were lower (P < 0.01) and fecal bile acids greater (P = 0.001) in large than small dogs. Antibiotic administration restored plasma and muscle taurine to initial concentrations and halved fecal bile acid excretion by dogs of both groups. Conclusions: Blood taurine concentration may not be a sensitive indictor of taurine depletion caused by low intake of bioavailable SAA in dogs, especially in large dogs. Taurine status and dietary SAA requirements of dogs may substantively depend on taurine loss mediated by intestinal microbiota.